Ten apples up on top! - LeSieg, Theo. 1904-1991.; McKie, Roy. (New York Beginner Books, 1989)
A lion, a dog, and a tiger balance apples on their heads.
Keywords: Animals -- Fiction; Counting; Stories in rhyme